REPRESENTASI DESA DALAM FILM-TARI âDONGENG DARI DIRAHâ: ANALISIS SEMIOTIKA BARTHESIAN - , Sapto Hudoyo; , Dr. Budiawan ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Film is a collaborative work that combines multiple art forms that are supported by technology producing images and sound. Every form of art donated the respective roles and support each other. Film is used as a means of messengers via meaningful visual language and narrative affirmed. A film raises aesthetic values and meanings by offering interpretation by its audience. Storytelling through choreography on the stage of post-production (editing) will compete in the pieces and bring new meaning, it makes a film-dance to be superior to the performances of dance in general. Dance became a means of creating a depth of meaning on purpose to be conveyed. By using a semiotic theory of meaning in dance-film âSocerres From Dirahâ having this rural setting can be perceived through the culture and beliefs of rural communities. Of the system of signs (signifier/expression and signified/contents), obtained connotative meaning work, trying, praying and expression of excitement for all the work done by rural communities in making a living for his family.